1991
DOI: 10.1254/jjp.55.437
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Proton Pump Inhibitor, AG-1749 (Lansoprazole), on Reflux Esophagitis and Experimental Ulcers in Rats.

Abstract: ABSTRACT-The effects of (±)-2- [[[3-methyl-4-(2,2,2-trifluoroethoxy-2-pyridyljmethyl]-sulfinyl]-1H-benzimidazole (lansoprazole, AG-1749) and famotidine on various experimental ulcers in rats were compared. AG-1749 inhibited reflux esophagitis; gastric lesions induced by water-immersion stress, aspirin or ethanol; and duodenal ulcers induced by cysteamine or mepirizole in a dose-dependent manner: the ID50 values were 0.7, 2.4, 0.7, 8.5, 1.1 and 0.3 mg/kg, p.o. or i.d., respectively. Famotidine inhibited reflux … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 20 publications
1
19
0
1
Order By: Relevance
“…[29] DER-induced esophagitis in rats DER was surgically induced in rats according to Hashimoto 2012. [30] Solid foods was withdrawn 1 day before and for 1 day after surgery.…”
Section: Dosage and Administrationmentioning
confidence: 99%
“…[29] DER-induced esophagitis in rats DER was surgically induced in rats according to Hashimoto 2012. [30] Solid foods was withdrawn 1 day before and for 1 day after surgery.…”
Section: Dosage and Administrationmentioning
confidence: 99%
“…Ferguson 19 developed a model in rats and other animal species, by occluding the duodenum below the pylorus, and associating with the administration of histamine. Nakamura et al 5 , Inatomi 6 and Omura 4 developed experimental models of acid and chronic reflux esophagitis by occluding the rumen and obstructing the pylorus. The model developed by Nakamura et al 5 had the disadvantage of causing extrinsic (mechanical) gastric obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental models of GERD are important to study the action of the acid and alkaline juices, as well as to evaluate the therapeutic efficacy of drugs and surgical techniques. The closure of the pylorus and of the rumen helped studying reflux esophagitis in rats, according to the models developed 4,5,6 . The authors also tested the therapeutic efficacy of different esophageal mucosa protective drugs.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, gastric acid plays a cru cial role in the development of the aspirin-induced gastric lesions (16). The gastric lesion induced by ethanol was markedly prevented by drugs increasing the defensive fac tors, while the lesion induced by aspirin was prevented by drugs inhibiting the aggressive factors such as gastric acid (17,18). Our previous studies have also shown that sucral fate, 16,16-dimethyl prostaglandin E2 and cetraxate, drugs increasing the defensive factors, effectively inhibit ed ethanol-induced gastric lesions (17,19).…”
Section: Discussionmentioning
confidence: 99%